Separator for electrochemical device and electrochemical device including the same
The separator with lithium-substituted sulfonic acid groups on inorganic particles effectively captures manganese ions, addressing capacity loss and deterioration in lithium-manganese-based electrochemical devices.
Patent Information
- Application Number
- JP2024518489
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-29
- Filing Date
- 2023-08-29
- Publication Date
- 2025-11-06
- Estimated Expiration
- 2043-08-29
AI Technical Summary
Manganese ions leach from lithium-manganese-based positive electrodes in electrochemical devices, leading to capacity loss and deterioration due to precipitation on the negative electrode surface.
A separator comprising a porous polymer substrate with first and second inorganic particles, where the second particles have sulfonic acid groups substituted with lithium cations, forming a coating layer to adsorb manganese ions effectively.
The separator enhances manganese ion adsorption capacity, reducing impurity deposition on the negative electrode and maintaining device performance.
Smart Images

Figure 0007765150000001 
Figure 0007765150000002 
Figure 0007765150000003
Abstract
Description
[Technical Field]
[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0108673, filed with the Korean Intellectual Property Office on August 29, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a separator for an electrochemical device and an electrochemical device including the same, and more particularly to a separator for minimizing capacity loss in an electrochemical device using a lithium manganese-based positive electrode active material. [Background technology]
[0003] Electrochemical devices convert chemical energy into electrical energy using electrochemical reactions, and recently, lithium secondary batteries have been widely used due to their high energy density, high voltage, long cycle life, and applicability in a variety of fields.
[0004] A lithium secondary battery includes an electrode assembly made of a positive electrode, a negative electrode, and a separator between the positive and negative electrodes. The electrode assembly is housed in a case together with an electrolyte. The positive electrode provides lithium ions, which then pass through a separator made of a porous material and move to the negative electrode. The negative electrode can be made of a carbon-based active material, which has an electrochemical reaction potential close to that of metallic lithium and allows for the insertion and desorption of lithium ions.
[0005] Positive electrode active materials may contain lithium and various metal or transition metal elements. For example, nickel improves the capacity of electrochemical devices, cobalt improves the capacity and cycle stability of electrochemical devices, manganese improves the stability of electrochemical devices, and aluminum improves the output characteristics of electrochemical devices. However, because nickel has poor thermal stability and both nickel and cobalt are expensive, there has been growing interest recently in lithium-manganese-based positive electrode active materials that contain manganese.
[0006] However, in electrochemical devices using a manganese-containing cathode active material, manganese ions may leach out of the cathode during charging and discharging. The leachable manganese ions migrate to the anode and precipitate as manganese-containing impurities on the surface of the anode, forming a non-uniform film, which reduces the capacity of the electrochemical device.
[0007] Therefore, research is being conducted on separators for use in electrochemical devices containing lithium-manganese-based active materials that can capture manganese ions leached from the positive electrode and prevent them from migrating to the negative electrode, thereby preventing deterioration of the negative electrode and the electrochemical device containing the same. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a separator for an electrochemical element that is capable of adsorbing manganese ions eluted from a positive electrode, as a separator for use in an electrochemical element containing a lithium-manganese-based active material. [Means for solving the problem]
[0009] In one aspect of the present invention, there is provided a separator for an electrochemical device containing a lithium-manganese-based active material, the separator comprising: a porous polymer substrate; first inorganic particles; and second inorganic particles having a larger specific surface area than the first inorganic particles. The separator comprises a first porous coating layer formed on a first surface of the porous polymer substrate and a second porous coating layer formed on a second surface of the porous polymer substrate, the second inorganic particles having sulfonic acid groups introduced onto their surfaces, at least some of the sulfonic acid groups having hydrogen cations substituted with lithium cations.
[0010] The first porous coating layer may include the first inorganic particles and the second inorganic particles in a weight ratio of 2:8 to 3:7.
[0011] The second inorganic particles may be mesoporous inorganic particles containing pores with an average diameter of 1.5 nm to 50 nm.
[0012] The first inorganic particles may be different from the second inorganic particles and may not contain pores.
[0013] The sulfonic acid group may be one or more selected from the group consisting of methanesulfonic acid, ethanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, naphthalenesulfonic acid, phenylbenzimidazolesulfonic acid, and 2-acrylamido-2-methylpropanesulfonic acid.
[0014] The first inorganic particles are BaTiO3, BaSO4, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, YO3, SiO2, Al2O3, AlOOH, Al(OH)3, SiC, and TiO2.
[0015] The first porous coating layer may further include a water-based polymer binder, which may bind the first inorganic particles to each other, the second inorganic particles to each other, and the first inorganic particles to the second inorganic particles to form interstitial volumes formed in the gaps between the inorganic particles.
[0016] The aqueous polymer binder may be one or more selected from the group consisting of acrylic polymers, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, and polyimide.
[0017] The first porous coating layer may face the negative electrode of the electrochemical device.
[0018] The second porous coating layer may contain the first inorganic particles and may not contain the second inorganic particles.
[0019] The lithium manganese-based active material is Li 1+x Mn 2-x O4 (0 ≦ x ≦ 0.33), LiMnO3, LiMn2O3, LiMnO2, LiNi 1-x Mn x O2 (0.01 ≦ x ≦ 0.3), LiMn 2-x M x O2 (M = Co, Ni, Fe, Cr, Zn or Ta, and 0.01 ≦ x ≦ 0.1), Li2Mn3MO8 (M = Fe, Co, Ni, Cu or Zn), LiNi x Mn 2-x O4 (0 < x < 0.5) and one or more positive electrode active materials selected from the group consisting of LiMn2O4.
[0020] The average specific surface area of the first inorganic particles and the second inorganic particles contained in the first porous coating layer may be 500 m 2 / g to 700 m 2 / g.
[0021] The first porous coating layer may have a thickness of 1 μm to 6 μm.
[0022] The separator for an electrochemical device may have an adsorption rate of 20% to 50% for manganese ions eluted from the positive electrode containing the lithium manganese-based active material.
[0023] Another aspect of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator may be the separator for an electrochemical device according to the aspect of the present invention.
[0024] The electrochemical device may be a lithium secondary battery. [Effects of the Invention]
[0025] The separator for an electrochemical device according to the present invention introduces sulfonic acid groups onto the surfaces of inorganic particles contained in a porous coating layer, and substitutes hydrogen cations contained in at least some of the sulfonic acid groups with lithium cations, thereby providing improved manganese ion adsorption capacity compared to conventional separators.
[0026] In addition, the separator for an electrochemical device according to the present invention provides improved manganese ion adsorption capacity compared to conventional separators by controlling the content ratio of inorganic particles having sulfonic acid groups introduced therein and inorganic particles having no sulfonic acid groups introduced therein, and the position of the porous coating layer containing the inorganic particles having sulfonic acid groups introduced therein. DETAILED DESCRIPTION OF THE INVENTION
[0027] Hereinafter, each configuration of the present invention will be described in more detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0028] As used herein, the term "comprising" is used to list materials, compositions, devices, and methods useful in the present invention, but is not intended to be limiting to the listed examples.
[0029] As used in this specification, the terms "about" and "substantially" are used to mean a range of values or degrees or their approximations, taking into account inherent manufacturing and material tolerances, and are used to prevent infringers from unfairly exploiting the disclosure content in which precise or absolute values provided to facilitate understanding of the present invention are mentioned.
[0030] As used herein, "electrochemical device" refers to a primary battery, a secondary battery, a supercapacitor, and the like.
[0031] Unless otherwise specified, the term "particle size" used in this specification refers to D50, which is the particle size corresponding to 50% in the cumulative particle number distribution according to particle size.
[0032] One embodiment of the present invention provides a separator for an electrochemical device, comprising a porous polymer substrate, first inorganic particles, and second inorganic particles having a larger specific surface area than the first inorganic particles, a first porous coating layer formed on a first surface of the porous polymer substrate, and a second porous coating layer formed on a second surface of the porous polymer substrate. The second inorganic particles have sulfonic acid groups introduced onto their surfaces, at least some of the sulfonic acid groups having hydrogen cations substituted with lithium cations, and the electrochemical device comprises a lithium-manganese-based active material.
[0033] The porous polymer substrate electrically insulates the positive and negative electrodes to prevent short circuits and provides pores through which lithium ions can pass. The porous polymer substrate may be resistant to the organic solvent of the electrochemical device's electrolyte. For example, the porous polymer substrate may include, but is not limited to, polymer resins such as polyolefins (e.g., polyethylene, polypropylene, and polybutene), polyvinyl chloride, polyethylene terephthalate, polycycloolefins, polyethersulfone, polyamides, polyimides, polyimideamides, polyaramids, polycycloolefins, nylons, polytetrafluoroethylenes, and copolymers or mixtures thereof. Preferably, the porous polymer substrate includes a polyolefin-based polymer, which has excellent slurry applicability for forming a porous coating layer and is advantageous for producing a thin separator.
[0034] The thickness of the porous polymer substrate may be 1 μm to 100 μm, preferably 1 μm to 30 μm, and more preferably 15 μm to 30 μm. The porous polymer substrate may include pores with an average diameter of 0.01 μm to 10 μm. By adjusting the thickness of the porous polymer substrate within the above range, the volume of the electrochemical device can be minimized and the amount of active material contained in the electrochemical device can be increased while electrically insulating the positive and negative electrodes.
[0035] A porous coating layer (described below) is formed by coating at least one surface of the porous polymer substrate with a slurry and drying the coating. The slurry may include inorganic particles, a polymer binder, a dispersion medium, etc. Prior to coating the slurry, the porous polymer substrate may be subjected to a surface treatment such as plasma treatment or corona discharge to improve impregnation with the electrolyte.
[0036] The separator for an electrochemical device may include the porous polymer substrate and a porous coating layer. A plurality of porous coating layers may be provided, including a first porous coating layer formed on a first surface of the porous polymer substrate and a second porous coating layer formed on a second surface of the porous polymer substrate. The first porous coating layer may be formed by applying a first slurry to the first surface of the porous polymer substrate and drying it, and the second porous coating layer may be formed by applying a second slurry to the second surface opposite the first surface and drying it.
[0037] The porous coating layer may include inorganic particles for improving the mechanical properties and insulating properties of the porous polymer substrate and a polymer binder for improving adhesion between the electrode and the separator. The polymer binder provides adhesion between the electrode and the separator while also binding adjacent inorganic particles and maintaining the binding. The inorganic particles may bind to adjacent inorganic particles to provide interstitial volumes, which are voids between the inorganic particles, and lithium ions may migrate through the interstitial volumes.
[0038] Specifically, the first porous coating layer may include first inorganic particles and second inorganic particles having a larger specific surface area than the first inorganic particles, and the second porous coating layer may include inorganic particles of the same or different type as the first inorganic particles, but may not include the second inorganic particles.
[0039] The first inorganic particles may form a porous coating layer with a uniform thickness and may not undergo a redox reaction within the operating voltage range of an electrochemical device to which they are applied. For example, the first inorganic particles may have one or more of lithium ion transport ability, piezoelectricity, and flame retardancy.
[0040] Inorganic particles having lithium ion conduction ability contain lithium elements but mean having the function of moving lithium ions without storing lithium. Inorganic particles having lithium ion conduction ability can transmit and move lithium ions due to a kind of defect existing inside the particle structure. Therefore, the lithium ion conductivity in the electrochemical device is improved, and thereby the performance of the electrochemical device can be enhanced.
[0041] For example, inorganic particles having lithium ion conduction ability include Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitrides such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glasses such as Li3PO4-Li2S-SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glasses such as LiI-Li2S-P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), LLZO-based such as Li7La3Zr2O 12 and may be one or more selected from the group consisting of these mixtures, but is not limited thereto.
[0042] Piezoelectric inorganic particles are non-conductors under normal pressure, but when a certain amount of pressure is applied, their internal structure changes, allowing electricity to pass through. These inorganic particles exhibit high dielectric constants (dielectric constants of 100 or greater). When tensioned or compressed by a certain amount of pressure, they generate charges, with one side becoming positively charged and the other side becoming negatively charged, creating a potential difference between the two sides. When an internal short circuit occurs between the positive and negative electrodes due to an external impact such as a local crush or a nail, the inorganic particles coated on the separator not only prevent direct contact between the positive and negative electrodes, but also generate a potential difference within the particles due to the piezoelectricity of the inorganic particles. This allows electrons to move between the positive and negative electrodes, i.e., a minute current to flow, resulting in a gradual voltage decrease in the electrochemical device and improved safety.
[0043] For example, inorganic particles with piezoelectric properties include BaTiO3, BaSO4, Pb(Zr,Ti)O3 (PZT), and Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), HfO2 (hafnia), and mixtures thereof, but are not limited thereto.
[0044] The flame-retardant inorganic particles can impart flame-retardant properties to the separator or prevent a sudden rise in temperature inside the electrochemical device.
[0045] For example, the flame-retardant inorganic particles may be, but are not limited to, one or more selected from the group consisting of Sb2O3, Sb2O4, Sb2O5, SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, SiO2, Al2O3, AlOOH, Al(OH)3, SiC, TiO2, H3BO3, HBO2, and mixtures thereof.
[0046] The first inorganic particles may have an average particle size of 50 nm to 5,000 nm, preferably 200 nm to 1,000 nm, and more preferably 300 nm to 700 nm. If the average particle size of the first inorganic particles is less than 50 nm, an additional polymer binder is required to bond the inorganic particles, which is disadvantageous in terms of electrical resistance. If the average particle size of the first inorganic particles exceeds 5,000 nm, the surface uniformity of the coating layer decreases, and protruding particles after coating may damage the separator and electrodes during lamination, causing a short circuit. The specific surface area of the first inorganic particles is 1 m 2 / g or 50m 2 / g Preferably, the first inorganic particles do not contain pores.
[0047] The second inorganic particles may have a larger specific surface area, including pores, than the first inorganic particles, and can substantially impart manganese ion adsorption properties to the first porous coating layer. The second inorganic particles may be mesoporous inorganic particles having pores with an average diameter of 1.5 nm to 50 nm. Microporous inorganic particles with an average pore diameter of less than 1.5 nm have too small pore sizes, and macroporous inorganic particles with an average pore diameter of more than 50 nm have a small specific surface area, making it difficult to ensure manganese ion adsorption properties through the introduction of sulfonic acid groups.
[0048] The second inorganic particles may be of any type, provided that sulfonic acid groups (HSO) can be introduced onto their surfaces. Preferably, they may be different from the first inorganic particles, and more preferably, hydroxyl groups may be present on the surfaces of the inorganic particles prior to the introduction of sulfonic acid groups. The term "surface" encompasses both the surfaces of the second inorganic particles where no pores are formed and the internal surfaces of the pores. For example, the second inorganic particles may be one or more selected from the group consisting of mesoporous silica nanoparticles, mesoporous titania nanoparticles, mesoporous zirconia nanoparticles, and mesoporous alumina nanoparticles. Preferably, the second inorganic particles may be mesoporous silica nanoparticles.
[0049] The sulfonic acid group may be one or more selected from the group consisting of methanesulfonic acid, ethanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, naphthalenesulfonic acid, phenylbenzimidazolesulfonic acid, and 2-acrylamido-2-methylpropanesulfonic acid.
[0050] As hydrogen cations are released from the sulfonic acid groups introduced into the second inorganic particles, an attractive force acts between the electron-rich oxygen atoms and the manganese ions, thereby imparting manganese ion adsorption ability to the second inorganic particles.
[0051] At least some of the sulfonic acid groups may have hydrogen cations substituted with lithium cations. The substitution of lithium cations is performed by adding lithium hydroxide to a dispersion of the second inorganic particles having the sulfonic acid groups introduced therein and stirring the mixture. For example, hydrogen cations contained in 50% to 100% of the sulfonic acid groups present in the second inorganic particles may be substituted with lithium cations, but this is not limited thereto. The lithium cations are more easily released from the second inorganic particles than the hydrogen cations, thereby improving the manganese ion adsorption ability of the second inorganic particles. Furthermore, the lithium cations released from the second inorganic particles improve the lithium ion conductivity within the electrochemical device, thereby improving the performance of the electrochemical device.
[0052] The second inorganic particles have sulfonic acid groups introduced onto their surfaces, with at least some of the hydrogen cations of the sulfonic acid groups substituted with lithium cations. The average particle size may be 50 to 5,000 nm, preferably 200 to 1,000 nm, and more preferably 300 to 700 nm. If the average particle size of the second inorganic particles is less than 50 nm, an additional polymer binder is required to bond the inorganic particles together, which is disadvantageous in terms of electrical resistance. If the average particle size of the second inorganic particles exceeds 5,000 nm, the surface uniformity of the coating layer decreases, and protruding particles after coating may damage the separator and electrodes during lamination, resulting in short circuits. The specific surface area of the second inorganic particles is 500 m 2 / g or 1000m 2 / g.
[0053] The first porous coating layer may contain both the first inorganic particles and the second inorganic particles, thereby improving the mechanical properties of the porous polymer substrate and providing manganese ion adsorption capability. Specifically, the first porous coating layer may contain the first inorganic particles and the second inorganic particles in a weight ratio of 2:8 to 3:7. If the first inorganic particles are contained in an excessive amount relative to this ratio, the specific surface area of the first porous coating layer decreases rapidly, and the manganese ion adsorption capability decreases at a rate greater than the decrease in the specific surface area. If the second inorganic particles are contained in an excessive amount relative to this ratio, thermal shrinkage of the separator may occur due to a decrease in thermal stability. In a first porous coating layer satisfying this ratio, the average specific surface area of the first inorganic particles and the second inorganic particles may be 500 m or less. 2 / g or 700m 2 / g.
[0054] The porous coating layer may include a water-based polymer binder as a polymer binder. The weight-average molecular weight of the water-based polymer binder may be 10,000 to 10,000,000. For example, the water-based polymer binder may be one or more selected from the group consisting of acrylic polymers, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymers, and polyimides.
[0055] For example, the first porous coating layer may include an acrylate-based polymer as a water-based polymer binder, and the water-based polymer binder may bind the first inorganic particles to each other, the second inorganic particles to each other, and the first inorganic particles to the second inorganic particles, thereby forming interstitial volumes formed in the gaps between the inorganic particles.
[0056] The thickness of the first porous coating layer may be 1 μm to 6 μm. If the thickness of the first porous coating layer is less than 1 μm, problems occur in which impurities including manganese are precipitated in the negative electrode. If the thickness of the first coating layer exceeds 6 μm, the manganese ion adsorption efficiency does not increase significantly. Preferably, the thickness of the first porous coating layer may be 3 μm to 5 μm.
[0057] The first surface of the porous polymer substrate faces a negative electrode, and the second surface faces a positive electrode containing a lithium-manganese-based active material. The first porous coating layer is disposed to face the negative electrode of an electrochemical device, thereby delaying or reducing the deposition of impurities on the negative electrode surface.
[0058] The porous coating layer may further include a dispersant to further improve the dispersibility of the inorganic particles. The dispersant functions to maintain a uniform dispersion of the inorganic particles within the polymer binder during slurry preparation. For example, the dispersant may be one or more selected from the group consisting of oil-soluble polyamines, oil-soluble amine compounds, fatty acids, fatty alcohols, sorbitan fatty acid esters, tannic acid, and pyrogallol. When the slurry includes a dispersant, the porous coating layer may include the dispersant in an amount of 5 wt % or less.
[0059] The slurry may contain inorganic particles and polymer binder in a weight ratio of 90:10 to 10:90, preferably 80:20 to 20:80. If the weight ratio is outside this range, the movement of the polymer binder in the porous coating layer is hindered, and sufficient adhesive strength between the electrode and the separator cannot be ensured.
[0060] In another embodiment of the present invention, there is provided an electrochemical device including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the separator being the separator for an electrochemical device according to the above embodiment. For example, the electrochemical device may be a lithium secondary battery including a positive electrode containing a lithium manganese-based positive electrode active material.
[0061] The positive electrode and the negative electrode may each be formed by coating and drying an active material on at least one surface of a current collector. The current collector may be made of a conductive material that does not induce chemical changes in the electrochemical device. For example, the positive electrode current collector may be made of, but is not limited to, aluminum, nickel, titanium, calcined carbon, stainless steel, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. For example, the negative electrode current collector may be made of, but is not limited to, copper, nickel, titanium, calcined carbon, stainless steel, or copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The current collector may be in various forms, such as a thin metal plate, film, foil, net, porous material, or foam.
[0062] The lithium manganese-based positive electrode active material may contain neither nickel nor cobalt, or may contain only one of nickel and cobalt. For example, the lithium manganese-based positive electrode active material may contain Li 1+x Mn 2-x O4(0≦x≦0.33), LiMnO3, LiMn2O3, LiMnO2, LiNi 1-x Mn x O2(0.01≦x≦0.3), LiMn 2-x M x O2 (M = Co, Ni, Fe, Cr, Zn or Ta, 0.01≦x≦0.1), Li2Mn3MO8 (M = Fe, Co, Ni, Cu or Zn), LiNi x Mn 2-xIt may be one or more selected from the group consisting of O4 (0 < x < 0.5) and LiMn2O4. Preferably, the lithium manganese-based cathode active material may be an LMO-based active material containing only lithium and manganese.
[0063] The anode active material includes carbon such as graphitizable carbon and graphite-based carbon; Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. may be included, but are not limited thereto.
[0064] The electrochemical device includes a separator arranged such that the first porous coating layer faces the positive electrode, and the adsorption rate of manganese ions eluted from the positive electrode containing the lithium manganese-based active material may be 20% to 50%. The precipitation of impurities containing manganese at the negative electrode can be delayed or reduced within this range.
[0065] The electrochemical device can be manufactured by inserting the positive electrode, negative electrode, separator, and electrolyte into a case or pouch and sealing them. The shape of the case or pouch is not limited. For example, the electrochemical device may be a cylindrical, rectangular, coin-shaped, or pouch-shaped lithium secondary battery.
[0066] The lithium secondary battery is packed or modularized as a unit cell and can be used in small devices such as computers, mobile phones, and power tools, as well as medium to large devices such as power tools powered by battery-powered motors, electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), electric bicycles (E-bikes), electric two-wheeled vehicles including electric scooters, electric golf carts, and power storage systems.
[0067] The present invention will be described in more detail below with reference to specific examples and experimental examples. The following examples and experimental examples are provided to illustrate the present invention, and the present invention is not limited to these examples and experimental examples.
[0068] Example 1 [Preparation of first slurry]
[0069] Cetyltrimethylammonium chloride (cetyltrimethylammonium chloride) and tetraethyl orthosilicate (TEOS) were added as surfactants to a solution of water and ethanol mixed at a 1:1 weight ratio at room temperature (25°C), and the mixture was stirred for 10 minutes. Ammonia water was added to the stirred solution, and the mixture was left for one day. The precipitate was then filtered, washed, dried, and calcined to synthesize mesoporous silica nanoparticles with an average pore size of 10 nm and an average particle size of 300 nm.
[0070] 5 g of the synthesized mesoporous silica nanoparticles were added to 200 mL of dichloromethane and dispersed using ultrasound for 20 minutes. 2 mL of chlorosulfonic acid was added to 50 mL of dichloromethane and added dropwise to the mesoporous silica dispersion over a period of 2 hours. After the addition was complete, the mixture was stirred at room temperature for 15 hours and centrifuged to obtain a solid. The solid was washed five times with dichloromethane and dried in a vacuum at room temperature to obtain mesoporous silica nanoparticles with sulfonic acid groups. The mesoporous silica nanoparticles with sulfonic acid groups were added to a solution of 25 g of LiOH·H2O dissolved in 500 mL of distilled water and stirred for 12 hours. The hydrogen atoms in some of the sulfonic acid groups were replaced with lithium to produce second inorganic particles.
[0071] 100 mL of distilled water was prepared as an aqueous dispersion medium at room temperature. An acrylic polymer binder (Toyo Ink's CSB130, 40% solids, 177 nm particle size), carboxymethyl cellulose (GLCHEM's SG-L02), and a wetting agent were dispersed in the aqueous dispersion medium at a weight ratio of 8:5:1 to prepare a slurry for forming an organic / inorganic composite porous coating layer. 6 g of alumina with an average particle size of 500 nm as first inorganic particles and 24 g of the second inorganic particles were added to the slurry (weight ratio of first inorganic particles to second inorganic particles = 2:8) and stirred for 120 minutes to produce a first slurry in which the polymer binder and inorganic particles were dispersed.
[0072] [Preparation of second slurry] 100 mL of distilled water was prepared as an aqueous dispersion medium at room temperature. An acrylic polymer binder (Toyo Ink's CSB130, solids content 40%, particle size 177 nm), carboxymethyl cellulose (GLCHEM's SG-L02), and wetting agent were dispersed in the aqueous dispersion medium at a weight ratio of 8:5:1 to prepare a slurry for forming an organic / inorganic composite porous coating layer. 30 g of alumina with an average particle size of 500 nm was added to the slurry as inorganic particles and stirred for 120 minutes to produce a second slurry in which the polymer binder and inorganic particles were dispersed.
[0073] [Preparation of porous polymer substrate] Polypropylene film (PP) was used as the porous polymer substrate.
[0074] [Production of separation membrane] The first and second slurries were coated on both sides of a polypropylene film using a bar coater and then dried to prepare a separator. Each coating formed a porous coating layer with a thickness of 3 μm, resulting in a separator with a total thickness of approximately 15 μm.
[0075] Example 2 A separator was manufactured in the same manner as in Example 1, except that the first inorganic particles and the second inorganic particles were added in a weight ratio of 3:7 when the first slurry was manufactured.
[0076] Comparative Example 1 A separator was manufactured in the same manner as in Example 1, except that the first inorganic particles and the second inorganic particles were added in a weight ratio of 4:6 when the first slurry was manufactured.
[0077] Comparative Example 2 A separator was manufactured in the same manner as in Example 1, except that the first inorganic particles and the second inorganic particles were added in a weight ratio of 5:5 when the first slurry was manufactured.
[0078] Comparative Example 3 A separator was manufactured in the same manner as in Example 1, except that the first inorganic particles and the second inorganic particles were added in a weight ratio of 6:4 when preparing the first slurry.
[0079] Comparative Example 4 A separator was manufactured in the same manner as in Example 1, except that the first inorganic particles and the second inorganic particles were added in a weight ratio of 7:3 when the first slurry was manufactured.
[0080] Comparative Example 5 A separation membrane was prepared in the same manner as in Example 1, except that mesoporous silica nanoparticles having sulfonic acid groups introduced therein were used as the second inorganic particles.
[0081] Comparative Example 6 A separator was prepared in the same manner as in Example 1, except that both sides of a polypropylene film were coated with the second slurry.
[0082] Experimental example 1. Confirmation of the physical properties of the separation membrane The thicknesses of the first and second porous coating layers of the separators according to Examples 1 and 2 and Comparative Examples 1 to 6 were measured using a thickness gauge (Mitutoyo, VL-50S-B), and the average specific surface area of the inorganic particles contained in the first porous coating layer of each separator was measured and is shown in Table 1 below.
[0083] [Table 1]
[0084] Experimental Example 2: Confirmation of manganese ion adsorption performance of separation membrane The separation membranes according to Examples 1 and 2 and Comparative Examples 1 to 6 were respectively dissolved in a manganese sulfate solution (MnSO4) (initial Mn 2+ The membrane was completely immersed in a solution of 1,000 ppm of ammonium hydroxide (3,400 ppm concentration) for 24 hours, and then collected and dried. The dried membrane was analyzed by EDS (JEOL SEM, 15 kV) and the results are shown in Table 2 below.
[0085] After the separation membrane was recovered, the Mn remaining in the manganese sulfate solution was 2+ The ion concentration was measured to determine the Mn concentration for each separation membrane. 2+ The adsorption amounts are shown in Table 2 below.
[0086] [Table 2]
[0087] Experimental Example 3: Confirmation of cycle characteristics of electrochemical elements containing lithium manganese-based active materials
[0088] Lithium manganese composite oxide (LiMnO2), conductive material (Denka black), and binder (PVdF) were weighed out to a weight ratio of 95:2.5:2.5, and then mixed in N-methylpyrrolidone (NMP) to prepare a cathode active material slurry. The cathode active material slurry was coated on a 20 μm thick aluminum foil to a thickness of 200 μm, and then rolled and dried to prepare a cathode.
[0089] A 200 μm thick Li metal plate was used as the negative electrode, and the positive electrode and negative electrode were stacked with the separator of the example or comparative example sandwiched between them, and then inserted into an aluminum pouch.
[0090] 1 g of electrolyte containing 3 mol of vinylene carbonate (VC), 1.5 mol of propane sultone (PS), 1 mol of ethylene sulfate (ESa), and 1 mol of lithium salt LiPF6 as additives in a solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) mixed at a weight ratio of 3 / 7 was poured into the aluminum pouch, and the pouch was sealed to prepare a cell.
[0091] The fabricated cell was charged and discharged once at 0.1 C in a voltage range of 3.0 V to 4.35 V in a 25°C chamber, and then charged and discharged at 0.33 C 400 times to check the performance retention rate. The performance retention rate was calculated as the ratio of the discharge capacity after 400 cycles to the initial discharge capacity.
[0092] The resistance was measured before and after the 400 cycles to confirm the rate of increase in resistance.
[0093] [Table 3]
Claims
1. Porous polymer base material; a first porous coating layer including first inorganic particles and second inorganic particles having a specific surface area larger than that of the first inorganic particles, the first porous coating layer being formed on a first surface of the porous polymer substrate; and a second porous coating layer formed on a second surface of the porous polymer substrate; The first porous coating layer comprises: The first inorganic particles and the second inorganic particles are contained in a weight ratio of 2:8 to 3:7, The second inorganic particles are A separator for an electrochemical element comprising a lithium-manganese-based active material, the separator having sulfonic acid groups introduced onto its surface, at least some of the sulfonic acid groups being formed by substituting hydrogen cations with lithium cations.
2. The second inorganic particles are 2. The separator for an electrochemical device according to claim 1, wherein the separator is made of mesoporous inorganic particles having pores with an average diameter of 1.5 nm to 50 nm.
3. The sulfonic acid group is 2. The separator for electrochemical elements according to claim 1, wherein the separator is one or more selected from the group consisting of methanesulfonic acid, ethanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, naphthalenesulfonic acid, phenylbenzimidazolesulfonic acid, and 2-acrylamido-2-methylpropanesulfonic acid.
4. The first inorganic particles are Li 3 2O 4 、 x Ti y (2O 4 ) 3 (0<8<2、0<y<3),L- x Al y Ti z (2O 4 ) 3 (0<x<2、0<y<1、0<z<3), L- x Lạ y TiO 3 (0<8<2、0<y<3),L- x Ge y P z S w (0<x<4、0<y<1、0<z<1、0<w<5), L. x N y (0<8<4、0<y<2), L- x Si y S z (0<x<3、0<y<2、0<z<4), L. x P y S z (0<x<3、0<y<3、0<z<7), L- 7 Lạ 3 Zr 2 O 12 BaTiO 3 、BBO 4 、Pb(Zr,Ti)O 3 (PZT), Pb 1-x Lạ x Zr 1-y Ti y O 3 (>^ZT、0<8<1、0<y<1), Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT), HfO 2 、Sb 2 O 3 、Sb 2 O 4 、Sb 2 O 5 、SrTiO 3 、SnO 2 、CeO 2 、MgO、Mg(OH) 2、 NiO, CaO, ZnO, Zn 2 SnO 4 , ZnSnO 3 , ZnSn(OH) 6 , ZrO 2 , Y 2 O 3 , SiO 2 , Al 2 O 3 , AlOOH, Al(OH) 3 , SiC, TiO 2 , H 3 BO 3 and HBO 2 2. The separator for an electrochemical element according to claim 1, wherein the separator is one or more selected from the group consisting of:
5. The first porous coating layer comprises: Further comprising a water-based polymer binder; The aqueous polymer binder is 2. The separator for electrochemical elements according to claim 1, wherein the separator is configured to bond the first inorganic particles with each other, the second inorganic particles with each other, and the first inorganic particles with the second inorganic particles to form interstitial volumes formed by the gaps between the inorganic particles.
6. The aqueous polymer binder is 6. The separator for an electrochemical element according to claim 5, which is at least one selected from the group consisting of acrylic polymers, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymers, and polyimides.
7. The first porous coating layer comprises:
2. The separator for an electrochemical element according to claim 1, which faces the negative electrode of the electrochemical element.
8. The second porous coating layer comprises: The separator for an electrochemical device according to claim 7 , comprising the first inorganic particles but not the second inorganic particles.
9. The lithium manganese-based active material is Li 1+x Mn 2-x O 4 (0≦x≦0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 , LiNi 1-x Mn x O 2 (0.01≦x≦0.3), LiMn 2-x M x O 2 (M=Co, Ni, Fe, Cr, Zn or Ta, 0.01≦x≦0.1), Li 2 Mn 3 MO 8 (M=Fe, Co, Ni, Cu or Zn), LiNi x Mn 2-x O 4 (0<x<0.5) and LiMn 2 O 4 2. The separator for an electrochemical device according to claim 1, wherein the positive electrode active material is one or more selected from the group consisting of:
10. The first inorganic particles and the second inorganic particles included in the first porous coating layer have an average specific surface area of 500 m 2 / g to 700m 2 The separator for an electrochemical element according to claim 1, wherein the solubility is 1 / g.
11. The first porous coating layer comprises:
2. The separator for an electrochemical device according to claim 1, which has a thickness of 1 μm to 6 μm.
12. 2. The separator for an electrochemical device according to claim 1, wherein the separator has an adsorption rate of 20% to 50% for manganese ions eluted from a positive electrode containing the lithium manganese-based active material.
13. An electrochemical device comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, An electrochemical device, wherein the separator is a separator for an electrochemical device according to claim 1 .
Citation Information
Patent Citations
Nonaqueous electrolytic secondary battery
JP2002025527A
Slurry composition for separator of secondary battery and separator for secondary battery comprising the same
KR1020190050210A
Composition for non-aqueous secondary battery functional layer, functional layer for non-aqueous secondary battery, and non-aqueous secondary battery
US20180248162A1
Separator for lithium secondary battery, method for manufacturing same, and lithium secondary battery including same
US20190189987A1
Nonaqueous electrolyte battery inorganic particles and nonaqueous electrolyte battery
WO2017146237A1